LibriVoxDeEn: a corpus for German-to-English speech translation and speech recognition - Beilharz, Benjamin; Sun, Xin (Universität, 2019)
This dataset is a corpus of sentence-aligned triples of German audio, German text, and English translation, based on German audio books. The corpus...
Production date: 2019-10-17
Gesehen am 24.10.2019
Keywords: Forschungsdaten; Datenbank